The Correlation Between Working Posture and Work Duration and Non-Specific Neck Pain Symptoms in Computer User Employees - Andi Siti Irfa Fidia Mustafah; Nurhikmawaty Hasbiah; Andi Rahmaniar (Jambura Medical and Health Science Journal, 2023)
Introduction: Longer work processes with non-ergonomic working postures by employees who use computers can certainly cause musculoskeletal tension. One of the musculoskeletal disorders (MSDs) associated with computer use is complaints of non-specific neck pain caused by a non-ergonomic posture of the neck muscles over a long period, which causes muscle tension. This study aims to determine the relationship between working posture and duration of work using a computer on non-specific neck pain complaints among Hasanuddin University Rectorate employees.Method: A cross-sectional research design was carried out on 121 administrative employees aged 22 years who met the inclusion and exclusion criteria. Assessment of working posture uses the Baseline Risk Identification of Ergonomic Factor (BRIEF) questionnaire, and for non-specific neck pain complaints using the Nordic Body Map (NBM) questionnaire. The Spearman's rho correlation test analyzes the relationship between variables.Results: 49 out of 121 respondents had a high-risk working posture for non-specific neck pain, and 59 out of 121 had a long working duration. Working posture is positively correlated with symptoms of non-specific neck pain (p = 0.001; r = 0.598). In contrast, work duration did not correlate with symptoms of non-specific neck pain (p = 0.063; r = 0.169).Conclusion: High-risk working postures can predict the incidence of non-specific neck pain in office administration employees. This can be a consideration for office leaders to pay attention to the working posture of their employees.Key words: Duration, non-specific neck pain, working posture